2011
DOI: 10.17221/1293-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 enriched meat production on lipid peroxidation, antioxidative status, immune response and tibia bone characteristics in Japanese quail

Abstract: The objective of the present study was to research the effects of different supplemented dietary sources of n-3 polyunsaturated fatty acids (n-3 PUFA) to produce n-3 enriched meat on growth performance, meat quality, serum antioxidative status, immune response and tibia bone characteristics in Japanese quail. Three hundred 1-day-old Japanese quail chicks were randomly weighed and divided into five dietary treatments containing 0% oil (C, negative control), 2% vegetable oil (VO, positive control), 2% linseed oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
5
24
0
Order By: Relevance
“…Dry matter ranged from 26.2 to 26.7%, fat from 2.67 to 3.03% of DM, protein from 90.08 to 90.11% of DM and ash from 4.5 to 4.52% of DM in experimental group (Jankowski et al, 2012). In study by Ebeid et al (2011), no differences were also found in the content of dry matter, total protein, and crude ash in the breast muscles. Crespo and Esteve-Garcia (2001) found that different dietary fats had a significant effect on the ash content of thigh and breast muscle.…”
Section: Nutritional Compositionmentioning
confidence: 76%
“…Dry matter ranged from 26.2 to 26.7%, fat from 2.67 to 3.03% of DM, protein from 90.08 to 90.11% of DM and ash from 4.5 to 4.52% of DM in experimental group (Jankowski et al, 2012). In study by Ebeid et al (2011), no differences were also found in the content of dry matter, total protein, and crude ash in the breast muscles. Crespo and Esteve-Garcia (2001) found that different dietary fats had a significant effect on the ash content of thigh and breast muscle.…”
Section: Nutritional Compositionmentioning
confidence: 76%
“…That is why, in the present study, precise, accurate, and selective UPLC‐DAD method was used for evaluation of experimental diet influence on MDA formation in poultry meat. It should be noted that the yield of MDA formation depends on the concentration of PUFA in analyzed tissues . As the content of MDA in selenium supplemented groups (Group Se VI and SeY) compared with the control diet was ambiguous, two MDA indices were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies involving chickens show that FO is a valuable source of health‐promoting n‐3LPUFA that can be effectively transferred from feed to carcass lipids . Unfortunately, an increase in LPUFA levels in chicken carcasses was followed by an increase in the concentrations of lipid oxidation products or cholesterol oxidation products in raw and heat‐processed edible carcass parts of farm animals . The extent of lipid oxidation depends on number of factors, including the content of unsaturated fatty acids (UFA), prooxidants and antioxidants .…”
Section: Introductionmentioning
confidence: 99%
“…These differences between results of the two earlier trials and the current trial, however, could be explained by different location of the experimental facilities (Poland vs. Greece or Bulgaria). Even bigger difference was observed, when comparing current results to the work performed in Egypt: PUFA – 12%, MUFA – 46%, SFA – 42% (Ebeid et al ., ). Completely different values were reported by Montgomery et al .…”
Section: Discussionmentioning
confidence: 99%